PENGETAHUAN MAHASISWA UNIVERSITAS JEMBER TENTANG HIV/AIDS - Sinta Rachmawati; Rizqi Fauzia; Ema Rachmawati (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2022)
Human Immunodeficiency Virus (HIV) is the cause of Acquired Immune Deficiency Syndrome (AIDS). In Indonesia, the number of people infected with HIV reaches 50,282 while the number of people with AIDS is 7,036. East Java is the province with the highest number of HIV infection cases in Indonesia, while AIDS is in the third position. Jember Regency is the fifth largest district/city reporting AIDS cases in East Java Province. Knowledge is closely related to attitude. Good knowledge will affect a positive attitude, and vice versa. Stigma can be formed because there is no knowledge about how HIV/AIDS is transmitted. Ignorance causes fear so that an attitude of rejection is formed towards People Living with HIV/AIDS (PLWHA). This study aims to determine the knowledge of students at the University of Jember towards HIV/AIDS. This research was conducted in 2021 with a cross-sectional research design. Data was collected online based on a questionnaire adapted from Shokoohi et al. (2016). There were 378 students involved in the study. There were 24 questions about HIV/AIDS. The level of knowledge was divided into 3: low (correct score ≤ 12), medium (correct score 13-18) and high (correct score ≥ 19). A total of 80.2% of students have a high level of knowledge. Most of the respondents knew the main routes of HIV transmission and answered correctly about the prevention, diagnosis and treatment of HIV/AIDS. It is necessary to conduct a follow-up reseach in a broader population.